Perbedaan Kadar Caffeic Acid Phenethyl Ester Pada Propolis di Pasaran Wilayah Surakarta - Devina Noviani Pramono; Diding HP; Sri Hartati Hadinoto (Nexus Biomedika, 2013)
Background: Propolis is composed of several kinds of biological and pharmacological components that can work as immunomodulator, anti-tumor, anti-inflammation and antioxidants. This is mainly due to its chemical composition, one of which is Caffeic Acid Phenethyl Ester (CAPE). The amount and composition of its chemical components are mainly affected by several factors, some of which are the type of plant vegetation, geographical position, solvent, bees, seasonal factor, and weather. This leads to the different composition of chemical component among different brands of propolis. The same phenomenon happens in Surakarta. This research aimed to reveal either or not the different of CAPE level exist among different brand of propolis found in Surakartas market. Methods: This research was an observational analysis using purposive sampling method. Samples were six different brands of propolis found in Surakartas market. The samples were divided into 6 groups which were P1, P2, P3, P4, P5 and P6. Each group was measured five times. The measurement of CAPE level of each sample was done using UV Vis spectrophotometer with wave length of 700 nm using Prussian Blue method. Data analysis was done using one way Anova statistical test with SPSS 17.00 for Windows program. Results: The average level of CAPE found in propolis samples were P1 =11.5310.078 g/ml; P2 =5.4380.106 g/ml; P3 =12.5410.052 g/ml; P4 =9.0360.081 g/ml; P5 =10.5930.043 g/ml; and P6 =10.3660.133 g/ml with p value is below 0.001 (p < 0.001). Conclusions: There was a difference of CAPE level among propolis found in the market area of Surakarta. Keywords: CAPE, Propolis